2022
DOI: 10.1101/2022.07.05.498865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Cell RNA-Sequence Analyses Reveal Uniquely Expressed Genes and Heterogeneous Immune Cell Involvement in the Rat Model of Intervertebral Disc Degeneration

Abstract: Intervertebral disc (IVD) degeneration is characterized by a loss of cellularity, and changes in cell-mediated activity that drives anatomic changes to IVD structure. In this study, we use single cell RNA-sequencing analysis of cells extracted from the degenerating tissues of the rat IVD following lumbar disc puncture. Two control, uninjured IVDs (L2-3, L3-4) and two degenerated, injured IVDs (L4-5, L5-6) from each animal were examined either at two- and eight-week post-operative time points. The cells from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Chemokines released from degenerated IVD promote the in ltration and activation of immune cells such as T lymphocytes, B lymphocytes, macrophages, and mast cells, which can trigger a series of pathological responses in IVD cells, including promoting autophagy, aging, or apoptosis. On the other hand, it further ampli es the in ammatory cascade reaction and promotes the release of neurotrophic proteins, especially NGF, inducing nerve ber growth into the IVD, causing discogenic pain [17] . Previous studies have shown that immune cell in ltration (including Tregs and macrophages) is involved in the progression of IDD [18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…Chemokines released from degenerated IVD promote the in ltration and activation of immune cells such as T lymphocytes, B lymphocytes, macrophages, and mast cells, which can trigger a series of pathological responses in IVD cells, including promoting autophagy, aging, or apoptosis. On the other hand, it further ampli es the in ammatory cascade reaction and promotes the release of neurotrophic proteins, especially NGF, inducing nerve ber growth into the IVD, causing discogenic pain [17] . Previous studies have shown that immune cell in ltration (including Tregs and macrophages) is involved in the progression of IDD [18,19] .…”
Section: Introductionmentioning
confidence: 99%